New Tricoderma Species and Six Unrecorded Species of Endolichenic Fungi Isolated from Lichens - Seung-Yoon Oh; Yunhyeok Jang (Mycobiology, 2025)
During a project investigating the diversity of fungi associated with lichens, numerous strains of Sesquicillium and Trichoderma were isolated. Among these, several species were suspected to be unrecorded, prompting further study. In this study, the objective is to describe the taxonomic information of fungal species novel and previously unrecorded in South Korea. Through comprehensive molecular phylogenetic analysis and detailed morphological examination, seven fungal species were identified: Sesquicillium lasiacidis, Sesquicillium essexcoheniae, Trichoderma asperellum, Trichoderma paraobovatum sp. nov., Trichoderma rifaii, Trichoderma sparsum, and Trichoderma texanum. Molecular identification was conducted using ITS and LSU regions for Sesquicillium and ITS, EF1a, and RPB2 loci for Trichoderma, with phylogenetic analysis confirming their placement alongside type strains. These findings expand the known geographic distributions of these species and highlight the potential of lichen-associated fungi as reservoirs of bioactive compounds and enzymes with industrial and pharmaceutical applications.